Effects of controlled frequency breathing on maximal tethered swimming performance - Peyrebrune, M.; Robinson, J.; Lakomy, H.; Nevill, M. (Biomechanics and Medicine in Swimming IX, 2003)
The purpose of the present study was to examine the effect of CFB on sprint swimming performance and metabolism, using tethered swimming. It was hypothesised that tethered swimming performance would be compromised during CFB because of the detrimental changes in metabolism. The main finding was that performance was not affected by restricting breathing during sprinting, despite lower V.E, V.O2, V.CO2 and respiratory exchange ratio, in the B10 trial. The impact of the breathing action under fatigue conditions during sprint swimming may compromise stroke mechanics and therefore performance. A reduction in breathing frequency may help to avoid this to some extent, although swimmers should employ restricted breathing during sprint training in order to familiarise themselves with this practice and perhaps learn to cope better with the effects of hypercapnia. The hypothesis that CFB would compromise sprint tethered swimming performance was rejected.